Attenuated allergic airway hyperresponsiveness in C57BL/6 mice is associated with enhanced surfactant protein (SP)-D production following allergic sensitization - Atochina, Elena N (BioMed Central, 2003)
BACKGROUND: C57BL/6 mice have attenuated allergic airway hyperresponsiveness (AHR) when compared with Balb/c mice but the underlying mechanisms remain unclear. SP-D, an innate immune molecule with potent immunosuppressive activities may have an important modulatory role in the allergic airway response and the consequent physiological changes. We hypothesized that an elevated SP-D production is associated with the impaired ability of C57BL/6 mice to develop allergic AHR. METHODS: SP-D mRNA and protein expression was investigated during development of allergic airway changes in a model of Aspergillus fumigatus (Af)-induced allergic inflammation. To study whether strain dependency of allergic AHR is associated with different levels of SP-D in the lung, Balb/c and C57BL/6 mice were compared. RESULTS: Sensitization and exposure to Af induced significant airway inflammation in both mouse strains in comparison with naïve controls. AHR to acetylcholine however was significantly attenuated in C57BL/6 mice in spite of increased eosinophilia and serum IgE when compared with Balb/c mice (p < 0.05). Af challenge of sensitized C57BL/6 mice induced a markedly increased SP-D protein expression in the SA surfactant fraction (1,894 ± 170% of naïve controls) that was 1.5 fold greater than the increase in Balb/c mice (1,234 ± 121% p < 0.01). These changes were selective since levels of the hydrophobic SP-B and SP-C and the hydrophilic SP-A were significantly decreased following sensitization and challenge with Af in both strains. Further, sensitized and exposed C57BL/6 mice had significantly lower IL-4 and IL-5 in the BAL fluid than that of Balb/c mice (p < 0.05). CONCLUSIONS: These results suggest that enhanced SP-D production in the lung of C57BL/6 mice may contribute to an attenuated AHR in response to allergic airway sensitization. SP-D may act by inhibiting synthesis of Th2 cytokines.